Relações de trabalho e pós-modernidade: um estudo interdisciplinar sobre a flexibilização da legislação trabalhista no Brasil - Silva, Cássia Cristina Moretto da (2013)
The protection of work is a historical construction, in a world wide context, or in Brazil. The first rules related to labor are from the XIX century. It was on the XX century, however, that labor law was funded in most nations. There were many events that substantially influenced the development of the contemporary labor law, from which we could highlight: the different ways of organizing the work experienced by humanity (slavery, serfdom, guilds, industrial revolution), the different political regimes, the very emerge of labor law as an area of law able to protect and regulate the established relations between workers and employers and the different social conjectures experienced ( the post-modern condition, the globalization, the neoliberalism and the flexibility of the relations). In Brazil, the emergence of the labor law was considered as a consequence of two important historical facts in Brazilian´s political scene: the slavery abolition and the proclamation of the republic. However, it was only after the 30`s that the significant amount of normative production was developed. In addition to it, there was the inclusion of labor protection laws in Brazilian´s constitutions. This subject has received special attention from the constitutional legislator of 1988. The flexible element of labor relations was also included in the law which influenced very sharply Brazilian´s labor, social and economical contexts. Due to that, the easing of labor laws, understood as the ability of the parties evolved in a labor contract (workers and employers) to establish certain labor conditions, attending the related legal requirements, takes a prominent position. This phenomenon encountered opponents and defenders because of the sharp changes in the labor scene, due to its positive (guaranteeing employability, giving a bigger autonomy for parties to negotiate working conditions, increasing the number of jobs, reducing labor costs) or the present negative points (reduction of workers' rights and their working conditions, social and financial damage to the working class, volatility of the labor relations). In Brazil, the easing of the labor laws emerged as a possibility of negotiating some conditions of the working contract, through the labor union, in the cases authorized by law. Therefore, in this scenario, there is a special emphasis on the labor unions and the labor justice is presented as the courts with the mission of equalize different and conflictive interests. Some theorists emphasize the issue of flexicurity as part of the phenomenon of easing, while others highlight the worsening of labor relations. It’s in this context that this present object of study was produced, focusing on the analysis of the labor relations and the easing of Brazilian’s labor laws, considering the different factors of different orders that are related to this reality as well as the social circumstances experienced and also the economic and political settings of Brazil in the XX and XXI centuries.